2010
DOI: 10.1080/14786430903575157
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric behavior and PTCR effect in nanocrystallite PMN ferroelectric ceramics

Abstract: The ac behavior of a nanocrystallite lead magnesium niobate (PMN) ceramic sample was studied over a wide range of temperatures and frequencies. The results revealed a diffuse phase transition and very high dielectric constant at lower frequencies. The high value of the dielectric constant at lower frequencies is shown to be due to barrier layer formation. A positive temperature coefficient of resistivity (PTCR) was observed in the temperature dependence of the ceramic resistivity. The results are explained on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…From stress-strain curves, it seems that by increasing compression in unidirectional fiber orientation(0°), this bonding becomes greater and the role of matrix against microbuckling of fibres is more highlighted. As shown in the figure, significant nonlinear deformation was often observed before the maximum load, and this behavior was associated to the plastic deformation of the polymeric matrix [23,29]. [17], who reported that unidirectional glass/epoxy (%V f = 35%) composites achieved higher (c. a.…”
Section: Effect Of Fibre Orientations On Compressive Behavior Of Tmentioning
confidence: 93%
“…From stress-strain curves, it seems that by increasing compression in unidirectional fiber orientation(0°), this bonding becomes greater and the role of matrix against microbuckling of fibres is more highlighted. As shown in the figure, significant nonlinear deformation was often observed before the maximum load, and this behavior was associated to the plastic deformation of the polymeric matrix [23,29]. [17], who reported that unidirectional glass/epoxy (%V f = 35%) composites achieved higher (c. a.…”
Section: Effect Of Fibre Orientations On Compressive Behavior Of Tmentioning
confidence: 93%